BOUNDARY ELEMENT DETERMINATION OF STRAIN UNIFORM DISTRIBUTION CONDITIONS IN FORGINGS PRODUCED UNDER BROACHING BY RADIAL ROLLING-IMPRESSION DIES - Armenak V. Vovchenko (Advanced Engineering Research, 2012)
The boundary element analysis data of forging round cross-section blanks by the radial rolling-impression dies are presented. The effective technological parameter boundary values for the forging process which permit to lower the increase of the strain nonuniformity in forging cross section are defined. The numerical analysis data are put in the functional expressions making connection between the broaching technological parameters, notch parameters in the dies, and cross section in the blanks used.